Scooby-Doo 2 : monsters unleashed [videorecording (DVD)] - Gosnell, Raja; Roven, Charles; Suckle, Richard; Gunn, James, 1966-; Prinze, Freddie, Jr; Gellar, Sarah Michelle, 1977-; Lillard, Matthew, 1970-; Cardellini, Linda, 1975-; Green, Seth, 1974-; Boyle, Peter, 1935-2006; Nelson, Tim Blake; Silverstone, Alicia; et al. (Warner Home Video, 2004)
The reunited Mystery, Inc. team return to their hometown of Coolsville as heroes where the local criminology museum offers an exhibition of the many ghostly disguises used by villains they've subdued over the years. Their warm welcome is short lived when a mean-spirited reporter airs a series of stories calling the teams abilities into question. To make matters worse, a number of the weird creature costumes are coming to life and wrecking havoc on the people of Coolsville.